(untitled) (Ágora Journal, 2024)
This research discusses the Plínio Salgado and Cassiano Ricardo’s opinion – published in various articles in the newspaper Correio Paulistano – as cultural consumption of José Vasconcelos’ notion “cosmic race”. It is also important to highlight that the opinion articles discussed here outlined of the Brazilian’s position at modernis, in this paper named with the colors of the Brazilian flag (green and yellow). We also problematize how the Brazilian modernism proposed the reinterpretation of eugenics, which valued the contribution of indigenous people, Africans, and European immigrants to Brazilian racial formation. We analyze how the positions on miscegenation exposed in these texts served as a backdrop to inspire the writing of the poem Martim Cererê (1927) by Cassiano Ricardo. Thus, considering the predominance of whitening theories in the first years of the 20th century, we argue that the appropriations of José Vasconcelos’ thesis by the two modernist writers produced another result such as, for example, the “cosmic race’s” notion as an appreciation of miscegenation as opposed to race pure.